2016
DOI: 10.1017/s1474746415000706
|View full text |Cite
|
Sign up to set email alerts
|

Parental Involvement and Multi-Agency Support Services for High-Need Families in France

Abstract: This article examines developments in parenting and family support services in France. Drawing on qualitative empirical studies, the article considers two types of initiatives ‒ the Programmes for Educational Success (PRE) and parenting interventions delivered alongside child protection services. Both of these services are examples of new types of parenting and family support interventions in the French context targeted at ‘children at risk’, seeking to address and prevent problems of educational underachievem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Recent research literature on the YAP model highlights the importance of supporting parents directly and indirectly as a way of improving children and young people's outcomes (Brady et al, 2020; Jackson et al, 2021). Join‐Lambert (2016) and Williams and Segrott (2018) have highlighted how in recent decades support services tend to involve parents in the work that is done with their children and build on the strengths and competences of parents themselves to reinforce and develop their parenting roles. Dunst and Trivette (2009) identified that having a family focus, and not just focusing on the child as the unit of intervention, enables parents to acquire the knowledge and skills to be able to cope with daily living and improve their sense of mastery and control.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research literature on the YAP model highlights the importance of supporting parents directly and indirectly as a way of improving children and young people's outcomes (Brady et al, 2020; Jackson et al, 2021). Join‐Lambert (2016) and Williams and Segrott (2018) have highlighted how in recent decades support services tend to involve parents in the work that is done with their children and build on the strengths and competences of parents themselves to reinforce and develop their parenting roles. Dunst and Trivette (2009) identified that having a family focus, and not just focusing on the child as the unit of intervention, enables parents to acquire the knowledge and skills to be able to cope with daily living and improve their sense of mastery and control.…”
Section: Discussionmentioning
confidence: 99%
“…He (Garrett, 2007: 209–11) identifies similarities between different elements of the original FIPs and approaches used to address ‘asocial families’ in Germany in the 1930s and ‘socially weak’ and ‘anti-social’ families the Netherlands in the 1950s (see also De Regt, 1982; Van Wel, 1992). Projects targeting families – more specifically, parents – that combine elements of family support with some more challenging forms of intervention can also be found in France (Join-Lambert, 2016; Martin, 2015), Germany (Ostner and Stolberg, 2015) and Sweden (Lundqvist, 2015). This international focus on parenting practices in disadvantaged, marginalised, ‘troubled’ or ‘high-need’ families (Join-Lambert, 2016) demonstrates that the increasing political fixation with ‘family’ is not specific to the UK.…”
Section: International Iterationsmentioning
confidence: 99%
“…Projects targeting families – more specifically, parents – that combine elements of family support with some more challenging forms of intervention can also be found in France (Join-Lambert, 2016; Martin, 2015), Germany (Ostner and Stolberg, 2015) and Sweden (Lundqvist, 2015). This international focus on parenting practices in disadvantaged, marginalised, ‘troubled’ or ‘high-need’ families (Join-Lambert, 2016) demonstrates that the increasing political fixation with ‘family’ is not specific to the UK. Further discussion of international perspectives can be found in the Useful Sources section of this issue.…”
Section: International Iterationsmentioning
confidence: 99%